"Si l’arbre ne respirait pas, comment grandirait-il?" La conception du vivant pour les Gouro de Côte-d’Ivoire, exemple de l’arbre - Haxaire, Claudie (Anthropologica, 2022)
Taking the term ethnobiology in a literal sense, i.e., the study of "phenomena common to all living beings" from the viewpoint of the Gouro people (Mande southern group, Ivory Coast) who do not practise Cartesian dualism, our approach is to not disassociate the visible and the invisible parts of the world. Their conceptions of the different functions of the living world and its characteristics must be studied, a sort of ethnophysiology, taking "physiology" in its pre-Socratic meaning. This is the path that we have explored here, through the conception that the Gouro have of the life of trees, those singular beings, fixed to the ground by their roots. We subsequently give some examples of the consequences of these conceptions for therapeutic practices as well as for the interpretations that this population, now living in a zone of secondary growth which has been devastated by fire, can have of the ecological and climatic disruption of its environment.